Bystander Roles in Cyberbullying: A Mini-Review of Who, How Many, and Why - Polanco-Levicán, Karina; Salvo-Garrido, Sonia (Frontiers in Psychology, 2021)
Cyberbullying has progressively increased due to the massive use of the internet and social networks. Generally, bystanders constitute the largest group, occupying a key role in the evolution of the cyberbullying situation and in its consequences for the victim. Research shows different ways in which bystanders behave, suggesting different types of sub-roles associated with different study variables. The objective of this literature review is to identify and characterize the roles of bystanders in cyberbullying situations that involve adolescent students. To achieve this objective, a systematic search was carried out in the Web of Science, Pubmed and Scopus databases for articles published between 2015 - 2020, resulting in 233 articles. Articles were then selected by relevant title and summary. Subsequently, the inclusion and exclusion criteria were applied, resulting in a total of nine articles. The findings of this review allowed us to identify two to five types of bystanders, the largest type representing outsiders and the smallest representing assistants of the aggressor. The identified types of bystanders are characterized with respect to variables such as sex, age, previous experience, and empathy. The results are discussed considering the available theoretical and empirical evidence.